Scientific Ethical Integrity and Human Research Subjects Protections Non-compliance Remediation: Commentary on Practical Considerations and Implications - Ralph J Johnson (Journal of Human Health Research, 2022)
Medical science’s advancements depend on preserving its credibility and the public trust, though as a human institution it is fallible and liable to ethical breaches that can void public confidence and support. There is no more egregious ethical departure than deviations / violations of Human Research Subjects Protections (i.e., non-compliance), which is remarkable given they are fairly widespread and often repeated. Once uncovered, this generally should result in the research’s suspension or termination. Yet, there is a third option to preserve valuable and worthy research that went awry due to lapses in Human Research Subjects Protections, specifically, Remediation. Due to the sequestered nature of Remediation, little has been reported on its processes, and practically nothing, regarding practical considerations, recommendations, and implications for the remediation workers themselves—for this line of work is perilously risky. This commentary reports some of those best-practices, “first-hand grittier in-the-trenches” informed practical lessons learned. Implications are discussed in the interest of improving the reasonable, balanced, and competent ethical conduct of research, addressing / avoiding Human Subjects Protections ethical non-compliance, and avenues for further inquiry regarding Remediation.
Keywords: Human Research Subjects Protections